Perceptions of Public University Students Towards Online Classes During COVID-19 Pandemic in Bangladesh - Sarkar, Shyam Sundar; Das, Pranta; Rahman, Mohammad Mahbubur; Zobaer, M S (Frontiers in Education, 2021)
The severe disease outbreak COVID-19 pandemic impacted public health and safety and the educational systems worldwide. For fear of the further spread of diseases, most educational institutions, including Bangladesh, have postponed their face-to-face teaching. Therefore, this study explores public university student's perceptions towards online classes during the COVID-19 pandemic in Bangladesh. Data were collected among students of Islamic University, Kushtia, Bangladesh, through an online survey. The study followed both a qualitative and quantitative approach, where the survey technique was used as an instrument of data collection. Results showed that most students were facing difficulty participating in virtual classes and could not communicate with their friends correctly during online classes. They faced challenges in online schooling, and the majority of the students preferred conventional types of learning to virtual classes and did not understand the content of virtual classes easily. The study also explored that most students did not feel comfortable in online classes. Still, considering the present pandemic situation, they decided to participate in online classes to continue schooling. Besides, the study discovered that female students showed better real perceptions than male students regarding online classes, and urban students have more optimistic appreciation than rural students. Moreover, laptop or personal computer users showed more positive perceptions towards online education than mobile users. Furthermore, Broadband/ Wi-Fi users have more positive perceptions than mobile network users. These findings would be an essential guideline for governments, policymakers, technology developers, and university authorities for making better policy choices in the future.